2010
DOI: 10.1111/j.1365-2109.2010.02747.x
|View full text |Cite
|
Sign up to set email alerts
|

Culture possibilities of the razor clam Ensis arcuatus (Pharidae: Bivalvia)

Abstract: This study investigated razor clam Ensis arcuatus culture from larval rearing to commercial size to assess it's aquaculture potential. Broodstock was spawned several times in hatchery facilities to demonstrate that larval availability is not a constraint for hatchery production. Larval culture lasted 20 days, showing an average survival of 14.35%. The razor clam seed reached a size of 28.5 mm at 4 months. Seed culture is feasible; however, it is constrained by the fact that razor clams need to be buried. Highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Supply of bivalve spat is one of the major constraints to restocking or initiating farming of clams and other bivalves (da Costa, Darriba, Martínez‐Patin & Guerra ). Our study provides useful information for producing spat of the smooth venus clam in hatcheries, especially using a down‐welling circulation system during the settlement stage.…”
Section: Discussionmentioning
confidence: 99%
“…Supply of bivalve spat is one of the major constraints to restocking or initiating farming of clams and other bivalves (da Costa, Darriba, Martínez‐Patin & Guerra ). Our study provides useful information for producing spat of the smooth venus clam in hatcheries, especially using a down‐welling circulation system during the settlement stage.…”
Section: Discussionmentioning
confidence: 99%
“…Razor clams have a slender and thin‐bladed shell shape. They are extremely fast burrowers and they require a substrate to allow burrowing, which influences culture conditions needed in hatchery, nursery and on‐growing culture (da Costa, Darriba, Martínez‐Patiño & Guerra ).…”
Section: Introductionmentioning
confidence: 99%
“…Using seed 1.3 mm in length, da Costa and Martinez-Patiño (2009) achieved better survival when the rearing was done without substrate than when 2 types of sand were utilised. In E. arcuatus, recently da Costa et al (2011a) achieved the settlement of larvae on day 20, a survival from egg to newly settled postlarvae ranging between 4.8 and 24.8% (14.35% on average), and a very low (4.8%) survival from settlement (day 20) to 3-month-old spat (15.5 mm in length).…”
Section: Reproduction Larval and Post-larval Rearingmentioning
confidence: 99%
“…In experimental condition, E. arcuatus reached a length ranging from 90 to 100 mm (da Costa et al, 2011a) Froglia (1975) found that the size of 100 mm was reached in 2-year-old individuals. After 2 years, the growth is reduced as a consequence of the gametogenic activity both in E. arcuatus and in S. marginatus.…”
Section: Grow-outmentioning
confidence: 99%
See 1 more Smart Citation